Comparing the predictive performance of different lymph node staging systems for postoperative overall survival in patients with ampullary carcinoma - Li, Xun; Chen, Lin; Li, Junli (Frontiers in Surgery, 2023)
Aim: This study was to analyze and compare the predictive performance of the 7th and the 8th edition American Joint Committee on Cancer (AJCC) N staging system, lymph nodes ratio (LNR) and log odds of positive lymph node (LODDS) for the survival of patients with ampullary carcinomas (ACs). Method: This retrospective cohort study included patients with primary ACs after surgery from the Surveillance, Epidemiology, and End Results 2004-2015. Univariate and multivariate Cox proportional hazard models were used. The study population was divided into a training set and a testing set in a ratio of 7 to 3. The C-index and area under the curve (AUC) were used to compare the predictive performance of the four staging on overall survival (OS) in the training set and the testing set. Results: A total of 7,480 patients with primary ACs (1,178 survival and 1,128 death) were in this study. The average follow-up time was 41.1 months. N1 stage and N2 stage of the 8th edition AJCC N staging system, LNR staging (0-0.3), LNR (>0.3), LODDS (-2.4 to -0.8) and LODDS (>-0.8) were risk factors for OS after adjusting for age, race, pT stage, tumor size, grade, radiation, and insurance. The C-index of the 7th AJCC N staging was significantly lower than the C-index of the 8th AJCC N staging in the training set [0.608 vs. 0.629, P<0.001] and testing set [0.635 vs. 0.658, P<0.001]. The C-index of the LODDS staging was significantly higher than the C-index of the 8th AJCC N staging in the training set [0.641 vs. 0.629, P=0.034] and testing set [0.671 vs. 0.658, P=0.034]. LODDS staging predicted OS at 6 months [AUC=0.687], 12 months (AUC=0.692), and 48 months (AUC=0.709) better than the other three staging systems, and LNR staging (AUC=0.655) staging predicted OS at 24 months better than the other staging systems. Conclusion: The LNR and LODDS staging systems had better predictive performance for OS compared with the 8th edition AJCC N staging system. In particular, the LNR staging for 24-month OS prediction, and the LODDS staging for 6, 12, 24 and 48-month OS prediction showed good predictive performance.